Use of Flow Cytometry to Characterize the In Vivo Development of Neonatal Porcine Islets. (July 2018) - Lau, Hien; Corrales, Nicole; Flores, Antonio; Lee, Sarah; Zhang, Kevin; Alexander, Michael; Li, Shiri; Lakey, Jonathan
Abstract : Introduction: Characterization of the in vivo development of porcine islets and stem cells after transplant may aid to evaluate the quality of transplanted islets and stem cells. The purpose of this study is to characterize the cellular composition of neonatal porcine islets pre- and post-transplant into the kidney capsule of non-diabetic athymic nude mice. Materials and Methods: Non-diabetic athymic nude mice were transplanted with 6, 000 islet equivalents (IEQ) of either neonatal porcine islets (3-5 days old) Nephrectomy was performed 4 months after transplantation in both neonatal porcine islets to retrieve the islet graft for post-transplant evaluation. Pre- and post-transplant neonatal porcine islets were dissociated into single-cell suspension, stained with 7-AAD viability dye, pancreatic islet marker chromogranin A, insulin and glucagon antibodies to identify beta-cells and alpha cells, and analyzed through flow cytometry. Results: Before transplant, 48.8% of live neonatal pig islets were Chromogranin A positive, of which 7.59% were insulin positive and 1.60% were also glucagon positive. After 4 months of transplant, 56.8% of live neonatal porcine islets were positive for chromogranin A. The islets showed an increase in insulin positive populations to 13.1% and a decrease in glucagon positive population to 0.76%. Discussion: Neonatal porcine islets were positive for insulin and glucagon before transplant. An increase in beta-cell population was observed after transplantation Conclusion: Flow cytometry can potentially be useful to study the in vivo development of immature islets after transplantation to evaluate site-influenced changes in cell differentiation. Ongoing and future experiments will utilize this method to evaluate the development of porcine islets in diabetic animal models at different time points after transplantation, to maximize the resulting level of functional beta cells. UCI Department of Surgery. UCI Sue and Bill Gross Stem Cell Research Center. Brownstein Foundation. PADRE Foundation.